Repeated triplets complicated by monochorionic diamniotic twins following assisted reproduction: a case report and literature review - Bing Song; Zhe Wang; Yujie Chen; Chao Wang; Zhaolian Wei; Xiaojin He; Yunxia Cao (BMC, 2020)
Abstract Background Monochorionic twinning involves numerous maternal and fetal complications, triplets complicated by a monochorionic pair are at further increased risk. Here, we report a case of repeated triplets complicated by monochorionic diamniotic twins with successful pregnancy outcomes in a woman using autologous oocytes. Case presentation A 30-year-old female undergoing embryo transfer with fresh and frozen embryo cycles with autologous oocytes. The two cycles were confirmed by transvaginal ultrasound to result in successful clinical pregnancies of triplets complicated by a monochorionic twinning. The first pregnancy resulted in a singleton delivery after a selective reduction of the monochorionic pair. The subsequent pregnancy resulted in a dichorionic diamniotic twin pregnancy after the heartbeat of one of the monochorionic twin fetuses stopped at 43 days after embryo transfer. Both of the pregnancies ended with successful live births. Conclusions Our case report of repeated triplets with monochorionic twins suggests the potential causes and risk factors of monochorionic twinning in assisted reproduction and raises concern regarding the timing of multifetal pregnancy reduction.